Penerapan Pembelajaran Berbasis Masalah Mata Pelajaran IPA Terhadap Kemampuan Berpikir Kreatif dan Hasil Belajar Siswa - Hartati, Hartati; Fahruddin, Fahruddin; Azmin, Nikman (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
Various problems faced by all Integrated Science teachers at SMP country 5 Bima City are the lack of students' creative thinking skills, so that students' difficulties in learning activities, especially group discussions with the use of learning models that have not fully activated students, so far science teachers are still using learning models conventional group. The purpose of this study was to determine the application of problem-based learning in Integrated Science subjects to creative thinking skills and learning outcomes of class VIII students of SMP country 5 Bima City. The subjects in the study were students of class VIII 3 at SMP country 5 Bima City, as many as 26 students. The instrument used is an evaluation test of student learning outcomes that is given at the end of each cycle, an observation sheet about the implementation of learning that is used to see learning activities. The data obtained were analyzed using data analysis of students' creative thinking abilities to determine learning completeness. The results showed an increase in the percentage of scores in the first cycle which was mostly in the creative category of 17 students, while in the second cycle the highest percentage of scores was in the very creative category of 18 students. 61% of classical learning completeness in cycle I was declared incomplete, but increased in cycle II 80% was declared complete. Based on the results and discussion, it is concluded that the application of problem-based learning can improve the creative thinking skills of class VIII students of SMP country 5 Bima City.